Time of Arrival Error Estimation for Positioning Using Convolutional Neural Networks - Kirmaz, Anil; Şahin, Taylan; Michalopoulos, Diomidis S.; Ashraf, Muhammad Ikram; Gerstacker, Wolfgang (IEEE Wireless Communications and Networking Conference, WCNC, 2023)
Wireless high-accuracy positioning has recently attracted growing research interest due to diversified nature of applications such as industrial asset tracking, autonomous driving, process automation, and many more. However, obtaining a highly accurate location information is hampered by challenges due to the radio environment. A major source of error for time-based positioning methods is inaccurate time-of-arrival (ToA) or range estimation. Machine leaning (ML) techniques emerged as potential solutions to mitigate ToA-related errors. However, existing ML-based solutions either employ a set of features representing channel measurements only to a limited extent, or account for only device-specific proprietary methods of ToA estimation. In this paper, we propose a convolutional neural network (CNN) to estimate and mitigate the errors of a variety of ToA estimation methods utilizing channel impulse responses (CIRs). Based on real-world measurements from two independent campaigns, the proposed method yields significant improvements in ranging accuracy (up to 37%) of conventional ToA estimators, often eliminating the need of optimizing the underlying conventional methods.
CRIS-Team Scopus Importer:2023-06-02
Keywords: convolutional neural networks; high accuracy positioning; Time-of-arrival estimation